2021
DOI: 10.1038/s42003-021-02316-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the evidence for epigenetic regulation of environmental influences on child health across generations

Abstract: Environmental exposures, psychosocial stressors and nutrition are all potentially important influences that may impact health outcomes directly or via interactions with the genome or epigenome over generations. While there have been clear successes in large-scale human genetic studies in recent decades, there is still a substantial amount of missing heritability to be elucidated for complex childhood disorders. Mounting evidence, primarily in animals, suggests environmental exposures may generate or perpetuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 262 publications
(294 reference statements)
0
67
0
Order By: Relevance
“…Epigenetic marks are partly inherited (transmission of epigenetic marks from one generation to another) but are also the signature and reflection of exposure to environments throughout life, particularly the early environment during gestation and lactation, which is a very sensitive period to both internal and external factors. Indeed, epigenetic mechanisms represent a means through which environmental factors can leave long-lasting memory of past experiences ( Kundakovic and Jaric, 2017 ; Cirulli et al, 2020 ; Bellver-Sanchis et al, 2021 ; Breton et al, 2021 ). Although epigenetic modifications are often considered stable over time, epigenetic plasticity exists and may mediate adaptation to drastic environmental changes.…”
Section: Epigenetic Mechanisms Mediate Long-term Influence Of Environ...mentioning
confidence: 99%
“…Epigenetic marks are partly inherited (transmission of epigenetic marks from one generation to another) but are also the signature and reflection of exposure to environments throughout life, particularly the early environment during gestation and lactation, which is a very sensitive period to both internal and external factors. Indeed, epigenetic mechanisms represent a means through which environmental factors can leave long-lasting memory of past experiences ( Kundakovic and Jaric, 2017 ; Cirulli et al, 2020 ; Bellver-Sanchis et al, 2021 ; Breton et al, 2021 ). Although epigenetic modifications are often considered stable over time, epigenetic plasticity exists and may mediate adaptation to drastic environmental changes.…”
Section: Epigenetic Mechanisms Mediate Long-term Influence Of Environ...mentioning
confidence: 99%
“…This causality acquires an extra level of complexity when associations involved an environmental factor or lifestyle habits. Smoking has been widely associated with epigenetic alterations and increased risk of respiratory diseases (e.g., chronic obstructive pulmonary disease or asthma) or neurodevelopmental disorders (e.g., child attention-deficit/hyperactivity disorder) at a single generation but also in transgenerational inheritance [ 72 , 73 ]. However, studies involving different human cohorts did not allow for conclusions that a causal association between smoking, methylation and disease output exists [ 72 ].…”
Section: Current Ethical and Social Challenges Raised By Epigeneticsmentioning
confidence: 99%
“…Further, the findings of several studies have indicated that certain environmental exposures may impact the health of individuals for multiple generations following the initial insult (reviewed in Breton et al, 2021 ). Human and animal studies are beginning to examine multigenerational risk factors for ASD, defined here as any factors that are non-genetic but may include demographic/social factors, chemical exposures, medications, and medical conditions in the generations prior to the individual diagnosed with ASD.…”
Section: Introductionmentioning
confidence: 99%